2002
DOI: 10.1093/jac/dkf069
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PSE and OXA beta-lactamase genes in Pseudomonas aeruginosa using PCR-restriction fragment length polymorphism

Abstract: This approach is effective for screening P. aeruginosa for beta-lactamase gene carriage in epidemiological studies and for detecting new variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(84 citation statements)
references
References 28 publications
2
78
1
3
Order By: Relevance
“…The most common imported ␤-lactamases found among P. aeruginosa isolates are penicillinases belonging to the molecular class A serine ␤-lactamases (PSE, CARB, and TEM families). Within this group, enzymes belonging to the PSE family appear to be the most prevalent (14). The therapeutic impact of these penicillinases is relatively limited since they do not impact the clinical efficacy of extended-spectrum cephalosporins, monobactams, or carbapenems.…”
Section: Imported Resistance Mechanismsmentioning
confidence: 99%
“…The most common imported ␤-lactamases found among P. aeruginosa isolates are penicillinases belonging to the molecular class A serine ␤-lactamases (PSE, CARB, and TEM families). Within this group, enzymes belonging to the PSE family appear to be the most prevalent (14). The therapeutic impact of these penicillinases is relatively limited since they do not impact the clinical efficacy of extended-spectrum cephalosporins, monobactams, or carbapenems.…”
Section: Imported Resistance Mechanismsmentioning
confidence: 99%
“…The TEM-type enzymes described in P. aeruginosa, namely, TEM-4, TEM-21, TEM-24, and TEM-42, have been reported in rare isolates from France (3,13,25,30,42). A French survey indicated that only 10% of ticarcillin-resistant P. aeruginosa isolates (i.e., 1.9% of P. aeruginosa isolates) produce a TEMtype ␤-lactamase, whereas other narrow-spectrum ␤-lactamases (OXA and CARB) are more frequently encountered in that species (3).…”
Section: Epidemiologymentioning
confidence: 99%
“…The presence of OXA-type enzymes in Enterobacteriaceae has been described infrequently. OXA-1, OXA-2, OXA-10, and OXA-17 were previously reported in some parts of the world [21].…”
Section: Iso-electric Focusingmentioning
confidence: 58%